Purinergic Receptor (P2X7R): A Promising Anti-Parkinson’s Drug Target - Saivarshini Magham; M. Lalith Kumar; Praveen Thaggikuppe Krishnamurthy; Neenu Shaji; Aishwarya Reddy Ramakkamma (Advanced Pharmaceutical Bulletin, 2024)
Purpose: Parkinson’s disease (PD) is the fourth most common neurodegenerative disorder, characterized by degeneration of basal ganglia and a decrease in dopamine levels in the brain. Purinergic 2X7 receptors (P2X7Rs) serve as inflammation gatekeepers. They are found in both central and peripheral nervous systems (CNS & PNS), and are activated in glial cells during inflammation. Purinergic 2X receptors (P2XRs) have been extensively studied in recent decades, particularly P2X7R, because of their important role in neuroinflammation caused by selective overexpression in glial cells. As P2X7R and its selective antagonists may provide neuroprotection by preventing the release of inflammatory mediators such as IL-1, they have become a research focus in PD. The review covers structure, signalling, molecular mechanisms, neuroprotective role, and current developments of P2X7R antagonists in PD. Methods: A systematic analysis and review of the potential prospects of P2X7R antagonists in the treatment of PD were conducted by analyzing existing research data and reports published between 1996 and present. Results: There is a substantial body of evidence linking P2X7R to pathology of PD. As a result, P2X7R antagonists may have therapeutic potential in treatment of PD. Conclusion: P2X7R has been demonstrated as an efficacious target in PD. Recent advances in rational drug design have paved the way for development of therapeutically valuable P2X7R antagonists such as adamantyl cyanoguanides, small molecular weight compounds, and PET ligands for the treatment of PD. However, the exact molecular mechanism and therapeutic potential of P2X7R antagonists in treatment of PD are yet to be fully explored.